Entertaining free expression on public sidewalks: Are city ordinances kicking musical muses to the curb?. Issue 1 (3rd July 2018) - Sarapin, Susan H.; Morris, Pamela L.
ABSTRACT: Freedom of expression, provided by the First Amendment, is a core part of the foundation of our democracy. Yet those who use public places for artistic expression, such as music, are still fighting to benefit from this right, a right vital to their ability to earn a living from musical performances. Historically, both in the United States and elsewhere, buskers, those who perform on the streets for tips, have been subjected to unreasonable restrictions on the time, place, and manner of their speech, and, at times, outright banishment from constitutionally protected public fora. This article demonstrates why current restrictions on street performers constitute clear violations of free speech through an examination of historical restrictions, case law, and the current rules and regulations of four US cities. Obtaining an ostensibly permanent decision from the Supreme Court is not the solution for ensuring the free-speech rights of street performers. Rather, we present an example of model regulations that, if embraced by individual localities, can ensure proper protection for the First Amendment rights of musicians in public spaces.